2014
DOI: 10.1002/lite.201400027
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stability and non‐enzymatic browning reactions in Antarctic krill oil (Euphausia superba)

Abstract: Antarctic krill oil has gained much consideration recently due to its rich content of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in the form of phospholipids and its powerful antioxidant known as astaxanthin. To secure these valuable bioactive nutrients in krill oil, a gentle and immediate on-board processing of freshly captured krill is recommended. Compared to fish oil, krill oil has a more complex matrix, which leads to the formation of additional compounds from non-enzymatic browning reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 5 publications
2
15
0
Order By: Relevance
“…Our previous study reported that 2-methylbutanal increased gradually in krill oil as incubation time progressed. The same observation was obtained for 2heptanone and alkylpyrazines, but with a constant level thereafter [18,23]. Therefore, the presence of abovementioned volatiles might imply that lipid oxidation and non-enzymatic browning reactions indeed occurred during deodorization and/or storage of krill oil.…”
Section: Comparison Of Volatile Profiles Of Commercial Krill Oil Capssupporting
confidence: 73%
See 2 more Smart Citations
“…Our previous study reported that 2-methylbutanal increased gradually in krill oil as incubation time progressed. The same observation was obtained for 2heptanone and alkylpyrazines, but with a constant level thereafter [18,23]. Therefore, the presence of abovementioned volatiles might imply that lipid oxidation and non-enzymatic browning reactions indeed occurred during deodorization and/or storage of krill oil.…”
Section: Comparison Of Volatile Profiles Of Commercial Krill Oil Capssupporting
confidence: 73%
“…Group (B) Strecker-derived volatiles such as 3-methylbutanal (peak 4), 2-methylbutanal (peak 5), dimethyl disulfide (peak 8), and dimethyl trisulfide (peak 15). As suggested in our previous study [18,23], Strecker degradation is a minor pathway in non-enzymatic browning and involves the oxidative deamination of a-amino acids in the presence of a-dicarbonyl or carbonyl compounds derived either from reducing sugars or lipid oxidation products [25]. It is suggested that Strecker degradation of amino acids might occur via lipid peroxidation pathway in krill oil or to a lesser extent via Maillard reaction pathway in a matrix, where miniscule particles of krill exoskeleton are present [26].…”
Section: An Overview Of Volatiles Found In Commercial Krill Oil Capsulessupporting
confidence: 66%
See 1 more Smart Citation
“…This probably partly accounts for the reproduction‐enhancing effects of dietary krill meal because a previous study of ours has observed that a suitable n‐3/n‐6 PUFA ratio in the broodstock diet has considerable positive effects on spawning performance, egg and larval quality of tongue sole (Liang et al., ). Besides the high contents of n‐3 LC‐PUFA, krill meal is also rich in phospholipids (Saito et al., ), which could not only play important structural roles in biomembranes but also improve the bioavailability of LC‐PUFAs such as DHA and EPA (Lu et al., ; Ramprasath, Eyal, Zchut, Shafat, & Jones, ; Saleh et al., ). In the present study, given that the DHA content was not different among the diets, the increase in DHA concentration in eggs from krill meal‐supplemented groups probably evidenced the improvement of DHA bioavailability by the phospholipids in the krill meal.…”
Section: Discussionmentioning
confidence: 99%
“…These pyrroles may react to form brown colored polymers through aldol condensation or carbonyl‐amine polymerization, which later contribute to non‐enzymatic browning reactions. Hence, measurements of hydrophobic pyrroles and volatiles derived both from lipid oxidation and Strecker aldehydes are alternative ways to study oxidative stability of krill products .…”
Section: Introductionmentioning
confidence: 99%